The Influence of Service Quality on Consumer Satisfaction and Purchase Intention at The Legendary Restaurants in Malang - Andriyani, Dwi Retno (HABITAT, 2024)
The high-quality service is provided for customers to achieve customer’s satisfaction goals which actually could be mediated by their emotion. Therefore, to increase the customer satisfaction, the company need to pay attention to the quality service that is provided to add the positive emotions and reduce negative emotion. Consumer satisfaction also has an impact on customer loyalty that affects business development in the future. The customer satisfaction also has an impact on customer loyalty that affects the business development in the future. Similarly, the legendary restaurant nowadays has to survive in this onslaught era with many modern restaurants are emerging. Thus, it is necessary to improve the quality service in the terms of product quality, service providing, and the restaurant’s atmosphere. This research analyzed using SEM-PLS method by analyzing the tools used in WarpPLS. The result found that quality service has a positive impact on the positive emotions of the customers. It is compared If the quality service has a negative impact, it causes negative emotions also. So that, it could be guaranteed that the provided quality service succeeded in building positive emotions in customers. The positive emotions that experienced by the customers automatically defined their satisfaction and that thing also indirectly drive them to become a loyal customer. The Influence of Service Quality on Consumer Satisfaction and Purchase Intention at The Legendary.